2015
DOI: 10.1002/gamm.201510012
|View full text |Cite
|
Sign up to set email alerts
|

Linking atomistic, kinetic Monte Carlo and crystal plasticity simulations of single‐crystal tungsten strength

Abstract: Understanding and improving the mechanical properties of tungsten is a critical task for the materials fusion energy program. The plastic behavior in body‐centered cubic (bcc) metals like tungsten is governed primarily by screw dislocations on the atomic scale and by ensembles and interactions of dislocations at larger scales. Modeling this behavior requires the application of methods capable of resolving each relevant scale. At the small scale, atomistic methods are used to study single dislocation properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…[ 35,37 ] This tool has been used successfully to solve many problems, as detailed in the previous studies. [ 19,31,38–45 ] The recent steel matrix analysis with ceramic particles by Qayyum et al [ 46 ] has shown the viability of the DAMASK code to conduct a local deformation behavioral analysis.…”
Section: Micromechanical Modelingmentioning
confidence: 99%
“…[ 35,37 ] This tool has been used successfully to solve many problems, as detailed in the previous studies. [ 19,31,38–45 ] The recent steel matrix analysis with ceramic particles by Qayyum et al [ 46 ] has shown the viability of the DAMASK code to conduct a local deformation behavioral analysis.…”
Section: Micromechanical Modelingmentioning
confidence: 99%
“…Development of such a yield criterion for a uniaxial mechanical loading allows comparison with experimental data obtained at low temperatures during tension and compression tests. Despite the overestimation of the Peierls stress inherent to atomistic simulations, which is not resolved by accounting for non-Schmid effects as previously proposed [47], the criterion captures the relative variations of the yield stress with the orientation of the loading axis and manages to predict the active slip systems among all possible 1/2 111 {110} systems. It also accounts for the tension/compression asymmetry, predicting how the yield stress varies with the sign of the applied stress.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is not corrected by accounting for non-Schmid effects in the evaluation of the yield stress, as shown in Fig. 5, which was proposed as a possible explanation for such discrepancy in previous works [47,48]. Several other explanations have been proposed, among which a contribution of the zero-point energy [46].…”
Section: Yield Stress and Slip Activitymentioning
confidence: 93%
“…For the sake of completeness, we adopt the dislocation-densitybased constitutive law description from Cereceda et al (2016Cereceda et al ( , 2015, Stukowski et al (2015), and summarize it here. Interested readers are further referred to Cereceda et al (2016Cereceda et al ( , 2015Cereceda et al ( , 2013, Stukowski et al (2015), especially Cereceda et al (2016) for a complete formulation.…”
Section: Constitutive Lawmentioning
confidence: 99%